Application of SMES to enhance the dynamic performance of DFIG during voltage sag and swell - Yunus, A.; Masoum, Mohammad Sherkat; Abu-Siada, Ahmed (IEEE, 2012)
The integration of wind turbines into modern power grids has significantly increased during the last decade. Wind turbines equipped with doubly fed induction generators (DFIGs) have been dominating wind power installation worldwide since 2002. In this paper, a superconducting magnetic energy storage (SMES) unit is proposed to improve the dynamic performance of a wind energy conversion system equipped with DFIG during voltage sag and voltage swell events. The converter and the chopper of the SMES unit are controlled using a hysteresis current controller and a fuzzy logic controller, respectively. Detailed simulation is carried out using MATLAB/SIMULINK software to highlight the impact of the SMES unit in improving the overall system performance under voltage sag and voltage swell conditions.